Toll-like receptor activation and gene delivery efficiency in canine dendritic cells: a model for comparative oncology - Capellero, Sonia; De Maria, Raffaella; Piras, Lisa Adele; Marconato, Laura; Parisi, Lorenza; Mazzone, Eugenio; Marchiò, Caterina; Berrino, Enrico; Bellomo, Sara Erika; Sapino, Anna; Stola, Giovanni Paolo; Chiono, Valeria; et al. (Frontiers in Immunology, 2025)
ObjectivesDendritic cells (DCs) are pivotal antigen-presenting cells capable of bridging innate and adaptive immunity, making them promising candidates for cancer immunotherapy. While canine mature DCs (cmDCs) have been successfully generated from circulating mononuclear cells (CMCs) in healthy dogs, their derivation and immunomodulatory capacity in tumor-bearing dogs (TbDs) remain poorly characterized.MethodsIn this study, we evaluated the efficiency of cmDC generation from peripheral blood of both healthy donors (HDs) and TbDs and investigated their functional responses to Toll-like receptor (TLR) agonists and mRNA-based genetic modification.ResultsCD14+ monocytes were successfully isolated from peripheral blood using immunomagnetic sorting and differentiated into cmDCs using recombinant canine GM-CSF and IL-4. The differentiation efficiency was comparable between the two groups. In both cohorts, cmDCs upregulated key maturation markers (CD1a, CD80, CD83) and restored DLA class II expression in TbDs. Stimulation with LPS and R848 significantly increased CD80 and CD83 expression and triggered IL-12/p70 and IL-8 production, confirming the acquisition of a functional immunostimulatory phenotype. To assess their amenability to genetic engineering, cmDCs were transfected using DE-DOPE/mRNA lipoplexes. These lipoplexes exhibited favorable physicochemical properties and achieved robust mRNA delivery, resulting in 100% GFP-positive cells and >60% viability, outperforming electroporation in terms of cytocompatibility.ConclusionsOur findings demonstrate that cmDCs derived from both HDs and TbDs are phenotypically and functionally competent and can be efficiently transfected using a non-viral mRNA delivery system. This strategy offers a viable platform for the development of personalized, DC-based cancer vaccines in canine patients.